A vanadium battery electrode with multi-dimensional defect structure and preparation method thereof

By constructing a multi-dimensional defect structure and optimizing the microstructure on the electrode of all vanadium flow battery, the problems of small specific surface area and poor activity of the electrode are solved, and the energy and coulombic efficiency of the battery are significantly improved.

CN118888767BActive Publication Date: 2025-02-11HANGZHOU DEHAI AIKE ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411354615.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-11
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The electrode of all vanadium flow battery has a small specific surface area and poor activity, which leads to poor performance in the battery.

Method used

By performing steps such as self-precipitation of metal salts, heat treatment and pickling on the surface of the graphite felt electrode, a multi-dimensional defect structure is constructed, and the microstructure of the electrode is optimized through heteroatom introduction and gradient high-temperature treatment.

Benefits of technology

It significantly improves the electrochemical surface area and active sites of the electrode, and improves the energy efficiency and Coulomb efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118888767B_ABST
    Figure CN118888767B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a vanadium battery electrode with a multi-dimensional defect structure, comprising the following steps: washing graphite felt, drying, and obtaining a pure graphite felt electrode; dissolving a metal salt and an additive in deionized water to obtain a mixed solution; immersing the pure graphite felt electrode in the mixed solution, adding an alkaline solution, reacting, drying, and heat treating to obtain a graphite felt electrode modified with a metal oxide; dissolving a heteroatom source and a surfactant in deionized water to obtain a modified solution; immersing the graphite felt electrode modified with a metal oxide in the modified solution to obtain a precursor electrode; gradient calcining the precursor electrode, and washing it with an acid solution to obtain a vanadium battery electrode with a multi-dimensional defect structure. The electrode of the invention forms macroscopic surface defects and microscopic structural defects, and the organic combination of the two improves the efficiency of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of all-vanadium redox flow battery electrodes, and in particular relates to a vanadium battery electrode with a multi-dimensional defect structure and a preparation method thereof. Background Art

[0002] The vanadium liquid flow battery stack is mainly composed of electrodes, proton exchange membranes, bipolar plates, electrolytes and current collectors. It has strong scalability, inherent safety, reliable operation, and is easy to scale up, with good practical application prospects. The surface structure of the electrode has a significant impact on the electrochemical reaction activity, energy efficiency and cycle stability of the battery. Due to the presence of VO2 + and sulfuric acid, therefore, higher activity, conductivity and stability requirements are put forward for the electrode materials of all-vanadium flow batteries, while also requiring them to have excellent mechanical properties and low cost.

[0003] Carbon-based materials are widely used in vanadium flow batteries due to their good electrical conductivity, corrosion resistance, and low cost. Currently, graphite felt electrodes have disadvantages such as low electrochemical activity and small specific surface area, which lead to poor performance in vanadium flow batteries. Summary of the Invention

[0004] The purpose of the present invention is to provide a vanadium battery electrode with a multi-dimensional defect structure and a preparation method thereof, so as to solve the problems of small specific surface area and poor activity of vanadium battery electrodes.

[0005] The technical solution adopted in the present invention is as follows:

[0006] Step S1: washing the graphite felt with ethanol, deionized water, and acetone, respectively, and then drying it in a vacuum drying oven to obtain a pure graphite felt electrode;

[0007] Step S2: dissolving the metal salt and the additive in deionized water to obtain a mixed solution; immersing 4 to 8 parts by mass of a pure graphite felt electrode in 200 to 400 parts by mass of the mixed solution, then adding 20 to 80 parts by mass of an alkaline solution to carry out the reaction. After the reaction is completed, the graphite felt is removed, dried, and then heat-treated under inert gas protection to obtain a metal oxide-modified graphite felt electrode;

[0008] Step S3: dissolving a heteroatom source and a surfactant in deionized water to obtain a modified solution; immersing a metal oxide-modified graphite felt electrode in 100 to 400 parts by mass of the modified solution, allowing the electrode to stand for 10 to 30 minutes, then removing the electrode and drying the electrode to obtain a precursor electrode;

[0009] Step S4: Gradual calcination of the precursor electrode under inert gas protection, and after it is naturally cooled to room temperature, the obtained electrode is cleaned with acid solution, and after drying, a vanadium battery electrode with a multi-dimensional defect structure is obtained.

[0010] Preferably, the metal salt in step S2 is one of copper chloride, ferric sulfate, magnesium carbonate, aluminum chloride and zinc acetate, and the concentration of the metal salt in the mixed solution is 0.1-2 mol / L.

[0011] Preferably, the additive in step S2 is one of polyvinyl pyrrolidone, ethylenediaminetetraacetic acid, sodium polyphosphate and gluconic acid, and the mass concentration of the additive in the mixed solution is 0.2-2 g / L.

[0012] Preferably, the alkaline solution in step S2 is one of sodium carbonate solution, ammonia solution, disodium hydrogen phosphate solution and potassium hydroxide solution, and the concentration is 0.2-4 mol / L.

[0013] Preferably, in step S2, the inert gas is one of nitrogen, argon and helium, the heat treatment temperature is 200-500° C., and the heat treatment time is 2-4 hours.

[0014] Preferably, the heteroatom source in step S3 is one of urea, diphenylpropylphosphine, sodium lauryl sulfate, methylboric acid, thiourea and p-aminoazobenzene, and the concentration in the modification solution is 0.1-0.5 mol / L.

[0015] Preferably, the surfactant in step S3 is one of polyoxyethylene ethyl ether, ethylhexenol, glucitol, sodium p-styrene sulfonate and cetyltrimethylammonium bromide, and its mass concentration in the modified liquid is 1-5 g / L.

[0016] Preferably, the gradient calcination process in step S4 is: in an inert gas atmosphere, first keeping the temperature at 300-500°C for 1-3 hours, then keeping the temperature at 800-1000°C for 2-5 hours; the inert gas is one of nitrogen, argon and helium.

[0017] Preferably, the acid solution in step S4 is one of hydrochloric acid solution, oxalic acid solution, glycolic acid solution and aminosulfonic acid solution, and the concentration is 0.5-5 mol / L.

[0018] The beneficial effects of the invention include at least:

[0019] 1. The self-precipitation process of metal salts on the surface of graphite felt can achieve efficient adsorption of metal hydroxides on the surface of graphite felt fibers. The subsequent high-temperature heat treatment and acid washing process realizes the transformation and exfoliation of metal oxides. This process of strong adsorption followed by exfoliation constructs a macroscopic defect structure on the surface of graphite felt fibers, greatly increasing the electrochemical surface area of ​​the electrode, providing sufficient active sites for the subsequent change of vanadium ion valence state, and improving its energy efficiency and coulombic efficiency.

[0020] 2. By introducing different heteroatoms and subsequent gradient high-temperature treatment, atomic substitution and doping of heteroatoms on carbon fibers are achieved, and defect structures are introduced into the microstructure. The introduction of heteroatoms can optimize the physical and chemical properties of the carbon electrode surface and improve the performance of vanadium batteries, providing good conditions for energy conversion in all-vanadium liquid flow batteries and improving their energy efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of a method for preparing a vanadium battery electrode with a multi-dimensional defect structure according to the present invention;

[0022] Figure 2 This is a SEM image of the multi-dimensional defect vanadium battery electrode prepared in Example 1 of the present invention;

[0023] Figure 3 1 is the energy efficiency curve of the multi-dimensional defective electrodes obtained in Example 1 of the present invention and Comparative Example 4 after 20 cycles in the all-vanadium redox flow battery. DETAILED DESCRIPTION

[0024] like Figure 1 As shown, a method for preparing a vanadium battery electrode with a multi-dimensional defect structure includes the following steps:

[0025] Step S1: washing the graphite felt with ethanol, deionized water, and acetone, respectively, and then drying it in a vacuum drying oven to obtain a pure graphite felt electrode;

[0026] Step S2: dissolving a metal salt and an additive in deionized water to obtain a mixed solution; immersing 4 to 8 parts by mass of a pure graphite felt electrode in 200 to 400 parts by mass of the mixed solution, then adding 20 to 80 parts by mass of an alkaline solution to carry out a reaction, and after the reaction, removing the graphite felt, drying it, and then heat-treating it under inert gas protection to obtain a metal oxide-modified graphite felt electrode; the metal salt is one of copper chloride, ferric sulfate, magnesium carbonate, aluminum chloride, and zinc acetate, and the concentration of the metal salt in the mixed solution is 0.1 to 2 mol / L; the additive is one of polyvinylpyrrolidone, ethylenediaminetetraacetic acid, sodium polyphosphate, and gluconic acid, and the concentration of the additive in the mixed solution is 0.2 to 2 g / L; the alkaline solution is one of sodium carbonate solution, ammonia solution, disodium hydrogen phosphate solution, and potassium hydroxide solution, and the concentration is 0.2 to 4 mol / L; the inert gas is one of nitrogen, argon, and helium, the heat treatment temperature is 200 to 500°C, and the heat treatment time is 2 to 4 hours;

[0027] Step S3: dissolving a heteroatom source and a surfactant in deionized water to obtain a modification solution; immersing a metal salt-modified graphite felt electrode in 100 to 400 parts by mass of the modification solution, letting it stand for 10 to 30 minutes, then taking it out and drying it to obtain a precursor electrode; the heteroatom source is one of urea, diphenylpropylphosphine, sodium lauryl sulfate, methylboric acid, thiourea and p-aminoazobenzene, and its concentration in the modification solution is 0.1 to 0.5 mol / L; the surfactant is one of polyoxyethylene ethyl ether, ethyl hexenol, glucitol, sodium p-styrene sulfonate and hexadecyltrimethylammonium bromide, and its concentration in the modification solution is 1 to 5 g / L;

[0028] Step S4: Gradient calcining the precursor electrode under the protection of an inert gas, and after it is naturally cooled to room temperature, the obtained electrode is cleaned with an acid solution, and after drying, a vanadium battery electrode with a multi-dimensional defect structure is obtained; the gradient calcination process is: in an inert gas atmosphere, first keep it at a temperature of 300~500℃ for 1~3h, and then keep it at 800~1000℃ for 2~5h; the inert gas is one of nitrogen, argon and helium; the acid solution is one of hydrochloric acid solution, oxalic acid solution, hydroxyacetic acid solution and aminosulfonic acid solution, and the concentration is 0.5~5mol / L.

[0029] Example 1: This example includes the following steps:

[0030] Step S1: washing the graphite felt with ethanol, deionized water, and acetone, respectively, and then drying it in a vacuum drying oven to obtain a pure graphite felt electrode;

[0031] Step S2: dissolving copper chloride and polyvinyl pyrrolidone in deionized water to obtain a mixed solution, wherein the copper chloride concentration is 2 mol / L and the polyvinyl pyrrolidone mass concentration is 2 g / L; immersing 4 g of a pure graphite felt electrode in 200 mL of the mixed solution, followed by adding 20 mL of a 4 mol / L sodium carbonate solution to carry out the reaction. After the reaction, the graphite felt is removed, dried, and then heat-treated at 300° C. for 4 h under nitrogen protection to obtain a metal oxide-modified graphite felt electrode;

[0032] Step S3: dissolving sodium lauryl sulfate and ethyl hexenol in deionized water to obtain a modified solution, wherein the concentration of sodium lauryl sulfate is 0.3 mol / L and the concentration of ethyl hexenol is 4 g / L; immersing the metal oxide-modified graphite felt electrode in 400 mL of the modified solution, allowing it to stand for 30 minutes, then taking it out and drying it to obtain a precursor electrode;

[0033] Step S4: The precursor electrode is subjected to a gradient calcination process under nitrogen protection, wherein the gradient calcination process is: first, maintaining it at 300°C for 2 hours, and then maintaining it at 900°C for 2 hours. After cooling it naturally to room temperature, the resulting electrode is cleaned with a 3 mol / L oxalic acid solution and dried to obtain a vanadium battery electrode with a multidimensional defect structure;

[0034] Figure 2 The middle is a scanning electron microscope image of the vanadium battery electrode with a multi-dimensional defect structure in this embodiment, which clearly shows the unevenness and macroscopic defect structure of the graphite felt fiber surface, which is conducive to increasing the electrochemical area of ​​the graphite felt electrode and exposing more active sites; further, Figure 3 The figure below compares the energy efficiency of the multi-dimensional defect structure vanadium battery electrode prepared in Example 1 and that of Comparative Example 4 in an all-vanadium liquid flow battery. Its excellent energy efficiency may come from the combination of macroscopic defects and microscopic defects. While providing more active sites for electrochemical reactions, the two also improve the efficiency of the electrode structure in the transformation of vanadium valence states, thereby improving its related performance.

[0035] Example 2: This example includes the following steps:

[0036] Step S1: washing the graphite felt with ethanol, deionized water, and acetone, respectively, and then drying it in a vacuum drying oven to obtain a pure graphite felt electrode;

[0037] Step S2: dissolving ferric sulfate and ethylenediaminetetraacetic acid in deionized water to obtain a mixed solution, wherein the concentration of ferric sulfate is 2 mol / L and the concentration of ethylenediaminetetraacetic acid is 0.2 g / L; immersing 8 g of a pure graphite felt electrode in 400 mL of the mixed solution, followed by adding 60 mL of a 0.2 mol / L ammonia solution to carry out the reaction. After the reaction is completed, the graphite felt is removed, dried, and then heat-treated at 500° C. for 2 h under argon protection to obtain a metal oxide-modified graphite felt electrode;

[0038] Step S3: dissolving urea and glucitol in deionized water to obtain a modified solution, wherein the urea concentration is 0.5 mol / L and the glucitol concentration is 4 g / L; immersing the metal oxide-modified graphite felt electrode in 300 mL of the modified solution, standing for 15 minutes, then taking it out and drying it to obtain a precursor electrode;

[0039] Step S4: The precursor electrode is subjected to a gradient calcination process under argon protection, wherein the gradient calcination process is: first, maintaining it at 500°C for 1 hour, and then maintaining it at 1000°C for 3 hours. After cooling naturally to room temperature, the resulting electrode is cleaned with 0.5 mol / L hydrochloric acid solution and dried to obtain a vanadium battery electrode with a multidimensional defect structure.

[0040] Example 3: This example includes the following steps:

[0041] Step S1: washing the graphite felt with ethanol, deionized water, and acetone, respectively, and then drying it in a vacuum drying oven to obtain a pure graphite felt electrode;

[0042] Step S2: dissolving aluminum chloride and gluconic acid in deionized water to obtain a mixed solution, wherein the aluminum chloride concentration is 0.1 mol / L and the gluconic acid concentration is 0.5 g / L; immersing 5 g of a pure graphite felt electrode in 300 mL of the mixed solution, followed by adding 50 mL of a 1 mol / L potassium hydroxide solution to carry out the reaction. After the reaction is complete, the graphite felt is removed, dried, and then heat-treated at 400° C. for 3 h under helium protection to obtain a metal oxide-modified graphite felt electrode;

[0043] Step S3: dissolving diphenylpropylphosphine and sodium p-styrenesulfonate in deionized water to obtain a modified solution, wherein the concentration of diphenylpropylphosphine is 0.2 mol / L and the concentration of sodium p-styrenesulfonate is 1 g / L; immersing the metal oxide-modified graphite felt electrode in 100 mL of the modified solution, allowing it to stand for 20 minutes, then removing it and drying it to obtain a precursor electrode;

[0044] Step S4: The precursor electrode is subjected to a gradient calcination process under nitrogen protection, wherein the gradient calcination process is: first, maintaining it at 450°C for 1 hour, and then maintaining it at 800°C for 5 hours. After cooling naturally to room temperature, the resulting electrode is washed with a 5 mol / L glycolic acid solution and dried to obtain a vanadium battery electrode with a multidimensional defect structure.

[0045] Example 4: This example includes the following steps:

[0046] Step S1: washing the graphite felt with ethanol, deionized water, and acetone, respectively, and then drying it in a vacuum drying oven to obtain a pure graphite felt electrode;

[0047] Step S2: dissolving magnesium carbonate and sodium polyphosphate in deionized water to obtain a mixed solution, wherein the concentration of magnesium carbonate is 1.2 mol / L and the concentration of sodium polyphosphate is 0.5 g / L; immersing 7 g of a pure graphite felt electrode in 250 mL of the mixed solution, followed by adding 80 mL of a 2 mol / L sodium bicarbonate solution to carry out the reaction. After the reaction, the graphite felt is removed, dried, and then heat-treated at 200° C. under nitrogen protection for 4 h to obtain a metal oxide-modified graphite felt electrode;

[0048] Step S3: dissolving thiourea and cetyltrimethylammonium bromide in deionized water to obtain a modified solution, wherein the thiourea concentration is 0.1 mol / L and the cetyltrimethylammonium bromide concentration is 2 g / L; immersing the metal oxide-modified graphite felt electrode in 400 mL of the modified solution, allowing it to stand for 15 minutes, then removing it and drying it to obtain a precursor electrode;

[0049] Step S4: The precursor electrode is subjected to a gradient calcination process under nitrogen protection, wherein the gradient calcination process is: first, maintaining it at 350°C for 3 hours, and then maintaining it at 800°C for 2 hours. After cooling naturally to room temperature, the resulting electrode is cleaned with a 1 mol / L aminosulfonic acid solution and dried to obtain a vanadium battery electrode with a multidimensional defect structure.

[0050] Example 5: This example includes the following steps:

[0051] Step S1: washing the graphite felt with ethanol, deionized water, and acetone, respectively, and then drying it in a vacuum drying oven to obtain a pure graphite felt electrode;

[0052] Step S2: Dissolving zinc acetate and ethylenediaminetetraacetic acid in deionized water to obtain a mixed solution, wherein the zinc acetate concentration is 1.8 mol / L and the ethylenediaminetetraacetic acid concentration is 1 g / L; immersing 4 g of a pure graphite felt electrode in 350 mL of the mixed solution, followed by adding 40 mL of a 1.4 mol / L potassium hydroxide solution to carry out the reaction. After the reaction, the graphite felt is removed, dried, and then heat-treated at 350° C. under helium protection for 3 h to obtain a metal oxide-modified graphite felt electrode;

[0053] Step S3: dissolving p-aminoazobenzene and polyoxyethylene ethyl ether in deionized water to obtain a modified solution, wherein the p-aminoazobenzene concentration is 0.25 mol / L and the polyoxyethylene ethyl ether concentration is 4 g / L; immersing the metal oxide-modified graphite felt electrode in 100 mL of the modified solution, allowing it to stand for 30 minutes, then removing it and drying it to obtain a precursor electrode;

[0054] Step S4: The precursor electrode is subjected to a gradient calcination process under argon protection, wherein the gradient calcination process is: first, maintaining it at 400°C for 2.5 hours, and then maintaining it at 850°C for 4.5 hours. After cooling naturally to room temperature, the resulting electrode is cleaned with a 5 mol / L oxalic acid solution and dried to obtain a vanadium battery electrode with a multidimensional defect structure.

[0055] Example 6: This example includes the following steps:

[0056] Step S1: washing the graphite felt with ethanol, deionized water, and acetone, respectively, and then drying it in a vacuum drying oven to obtain a pure graphite felt electrode;

[0057] Step S2: dissolving copper chloride and sodium polyphosphate in deionized water to obtain a mixed solution, wherein the copper chloride concentration is 1.5 mol / L and the sodium polyphosphate concentration is 2 g / L; immersing 8 g of a pure graphite felt electrode in 400 mL of the mixed solution, followed by adding 60 mL of a 4 mol / L sodium carbonate solution to carry out the reaction. After the reaction is completed, the graphite felt is removed, dried, and then heat-treated at 400° C. for 3 h under helium protection to obtain a metal oxide-modified graphite felt electrode;

[0058] Step S3: dissolving methylboric acid and ethylhexenol in deionized water to obtain a modified solution, wherein the concentration of methylboric acid is 0.3 mol / L and the concentration of ethylhexenol is 2.5 g / L; immersing the metal oxide-modified graphite felt electrode in 200 mL of the modified solution, allowing it to stand for 20 minutes, then removing it and drying it to obtain a precursor electrode;

[0059] Step S4: The precursor electrode is subjected to a gradient calcination process under helium protection, wherein the gradient calcination process is: first, maintaining it at 400°C for 1.5 hours, and then maintaining it at 850°C for 4 hours. After cooling naturally to room temperature, the resulting electrode is cleaned with a 2.5 mol / L hydrochloric acid solution and dried to obtain a vanadium battery electrode with a multidimensional defect structure.

[0060] Comparative Example 1: This comparative example comprises the following steps:

[0061] Step S1: washing the graphite felt with ethanol, deionized water, and acetone, respectively, and then drying it in a vacuum drying oven to obtain a pure graphite felt electrode;

[0062] Step S2: dissolving polyvinyl pyrrolidone in deionized water to obtain a 2 g / L polyvinyl pyrrolidone solution; immersing 4 g of a pure graphite felt electrode in 200 mL of the polyvinyl pyrrolidone solution, followed by adding 20 mL of a 4 mol / L sodium carbonate solution to carry out the reaction. After the reaction is complete, the graphite felt is removed, dried, and then heat-treated at 300° C. for 4 h under nitrogen protection to obtain a graphite felt electrode without metal oxide modification;

[0063] Step S3: dissolving sodium lauryl sulfate and ethyl hexenol in deionized water to obtain a modified solution, wherein the concentration of sodium lauryl sulfate is 0.3 mol / L and the concentration of ethyl hexenol is 4 g / L; immersing a graphite felt electrode without metal oxide modification in 400 mL of the modified solution, standing for 30 minutes, then taking out and drying to obtain a precursor electrode;

[0064] Step S4: The precursor electrode is subjected to a gradient calcination process under nitrogen protection, wherein the gradient calcination process is: first, maintaining at 300°C for 2 hours, and then maintaining at 900°C for 2 hours. After cooling naturally to room temperature, a graphite felt electrode with a macro-defect-free structure is obtained.

[0065] Comparative Example 2: This comparative example comprises the following steps:

[0066] Step S1: washing the graphite felt with ethanol, deionized water, and acetone, respectively, and then drying it in a vacuum drying oven to obtain a pure graphite felt electrode;

[0067] Step S2: dissolving copper chloride and polyvinyl pyrrolidone in deionized water to obtain a mixed solution, wherein the copper chloride concentration is 2 mol / L and the polyvinyl pyrrolidone concentration is 2 g / L; immersing 4 g of a pure graphite felt electrode in 200 mL of the mixed solution, followed by adding 20 mL of a 4 mol / L sodium carbonate solution to carry out the reaction. After the reaction is completed, the graphite felt is removed, dried, and then heat-treated at 300° C. for 4 h under nitrogen protection to obtain a metal oxide-modified graphite felt electrode;

[0068] Step S3: dissolving ethyl hexenol in deionized water to obtain a modification solution with an ethyl hexenol concentration of 4 g / L; immersing the metal oxide-modified graphite felt electrode in 400 mL of the modification solution, allowing it to stand for 30 minutes, then taking it out and drying it to obtain a precursor electrode;

[0069] Step S4: The precursor electrode is subjected to a gradient calcination process under nitrogen protection, wherein the gradient calcination process is: first, maintaining at 300°C for 2 hours, and then maintaining at 900°C for 2 hours. After cooling naturally to room temperature, the resulting electrode is cleaned with a 3 mol / L oxalic acid solution and dried to obtain a graphite felt electrode with a microscopic defect-free structure.

[0070] Comparative Example 3: This comparative example comprises the following steps:

[0071] Step S1: washing the graphite felt with ethanol, deionized water, and acetone, respectively, and then drying it in a vacuum drying oven to obtain a pure graphite felt electrode;

[0072] Step S2: dissolving copper chloride and polyvinyl pyrrolidone in deionized water to obtain a mixed solution, wherein the copper chloride concentration is 2 mol / L and the polyvinyl pyrrolidone concentration is 2 g / L; immersing 4 g of a pure graphite felt electrode in 200 mL of the mixed solution, followed by adding 20 mL of a 4 mol / L sodium carbonate solution to carry out the reaction. After the reaction is completed, the graphite felt is removed, dried, and then heat-treated at 300° C. for 4 h under nitrogen protection to obtain a metal oxide-modified graphite felt electrode;

[0073] Step S3: dissolving sodium lauryl sulfate and ethyl hexenol in deionized water to obtain a modified solution, wherein the concentration of sodium lauryl sulfate is 0.3 mol / L and the concentration of ethyl hexenol is 4 g / L; immersing the metal oxide-modified graphite felt electrode in 400 mL of the modified solution, allowing it to stand for 30 minutes, then taking it out and drying it to obtain a precursor electrode;

[0074] Step S4: The precursor electrode is cleaned with a 3 mol / L oxalic acid solution, and after drying, a vanadium battery electrode with a multi-dimensional defect structure is obtained.

[0075] Comparative Example 4: blank graphite felt.

[0076] Specific surface area test method: Beijing Best BSD-660S model fully automatic physical adsorption instrument was used for testing. The graphite felt was cut into 2cm×2cm size, and the specific surface area test was performed under nitrogen to record the specific surface area.

[0077] Battery Testing Method: The multilayer core-shell structure modified graphite felts obtained in Examples 1-6 and Comparative Examples 1-4 were assembled into a battery stack. Battery charge and discharge performance tests were conducted under the same operating conditions, and the coulombic efficiency, voltage efficiency, and energy efficiency were recorded. The test results are shown in Table 1:

[0078] Table 1 Electrode and battery performance test table

[0079]

[0080] As can be seen from Table 1, compared with Comparative Examples 1 and 3, Examples 1-6 have higher specific surface area values. This is because the process of first adsorption and then stripping of the metal on the graphite felt surface causes the fibers to form a unique serrated defect structure, which can effectively increase the specific surface area of ​​the graphite felt electrode, thereby exposing more active sites and improving the coulombic efficiency and energy efficiency of the electrode in the all-vanadium liquid flow battery; compared with Comparative Example 2, Examples 1-6 have higher voltage efficiency and energy efficiency, which is mainly due to the introduction of heteroatoms in the microstructure and the construction of lattice defects in Examples 1-6. The introduction of heteroatoms enables the electrode to maintain a more stable structural structure, which is beneficial to improving the efficiency of the electrode structure in the transformation of vanadium valence states, thereby improving its energy efficiency. Compared with Examples 1-6 and blank graphite felt, Comparative Example 3 has lower voltage efficiency, energy efficiency and lower specific surface area, which shows that the final gradient heat treatment is an important step in forming macro defects and micro defects. Without this gradient heat treatment, the metal oxide cannot be converted into a metal element, and the heteroatom source is only adsorbed on the surface of the graphite felt, and the internal doping structure and atomic substitution cannot be formed, which has a negative effect on the performance improvement of the graphite felt. This combination and construction of macro defects and micro defects achieves the improvement of coulomb efficiency and energy efficiency.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a vanadium battery electrode having a multi-dimensional defect structure, characterized in that: At least the following steps are included: Step S1: washing the graphite felt with ethanol, deionized water and acetone respectively, and then drying it in a vacuum drying oven to obtain a pure graphite felt electrode; Step S2: dissolving a metal salt and an additive in deionized water to obtain a mixed solution; immersing 4 to 8 parts by mass of a pure graphite felt electrode in 200 to 400 parts by mass of the mixed solution, then adding 20 to 80 parts by mass of an alkaline solution to react, taking out the graphite felt after the reaction, drying it, and then heat-treating it under nitrogen or inert gas protection to obtain a metal oxide-modified graphite felt electrode; the metal salt is one of copper chloride, ferric sulfate, magnesium carbonate, aluminum chloride and zinc acetate, and the concentration in the mixed solution is 0.1 to 2 mol / L; the additive is one of polyvinyl pyrrolidone, ethylenediaminetetraacetic acid, sodium polyphosphate and gluconic acid, and the mass concentration in the mixed solution is 0.2 to 2 g / L; the inert gas is one of argon and helium; the heat treatment temperature is 200 to 500°C, and the time is 2 to 4 hours; Step S3: dissolving the heteroatom source and the surfactant in deionized water to obtain a modified solution; The metal oxide-modified graphite felt electrode is immersed in 100-400 parts by weight of the modification solution, and after standing for 10-30 minutes, it is taken out and dried to obtain a precursor electrode; the heteroatom source is one of urea, diphenylpropylphosphine, sodium dodecyl sulfate, methylboric acid, thiourea and p-aminoazobenzene; Step S4: Gradient calcining the precursor electrode under nitrogen or inert gas protection, and after it is naturally cooled to room temperature, the obtained electrode is cleaned with acid solution, and after drying, a vanadium battery electrode with a multi-dimensional defect structure is obtained; the gradient calcination process is: in a nitrogen or inert gas atmosphere, first keep it at a temperature of 300~500℃ for 1~3h, and then keep it at 800~1000℃ for 2~5h; the inert gas is one of argon and helium.

2. The method for preparing a vanadium battery electrode having a multi-dimensional defect structure according to claim 1, characterized in that: The alkaline solution in step S2 is one of sodium carbonate solution, ammonia solution, disodium hydrogen phosphate solution and potassium hydroxide solution, and the concentration is 0.2-4 mol / L.

3. The method for preparing a vanadium battery electrode having a multi-dimensional defect structure according to claim 1, characterized in that: In step S3, the concentration of the heteroatom source in the modified solution is 0.1-0.5 mol / L.

4. The method for preparing a vanadium battery electrode having a multi-dimensional defect structure according to claim 1, characterized in that: In step S3, the surfactant is one of polyoxyethylene ethyl ether, ethylhexenol, glucitol, sodium p-styrene sulfonate and hexadecyltrimethylammonium bromide, and the mass concentration in the modified liquid is 1-5 g / L.

5. The method for preparing a vanadium battery electrode having a multi-dimensional defect structure according to claim 1, characterized in that: The acid solution in step S4 is one of hydrochloric acid solution, oxalic acid solution, glycolic acid solution and aminosulfonic acid solution, and the concentration is 0.5-5 mol / L.

6. A vanadium battery electrode with a multi-dimensional defect structure, characterized in that: The vanadium battery electrode with a multi-dimensional defect structure is prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Composite electrode material and preparation method thereof, and applications of composite electrode material in all-vanadium flow battery

    CN106549162A

  • Electrode material for heteroatom-doped flow redox battery

    CN108539210A

  • Preparation method of modified alkaline total-iron flow battery electrode material

    CN117374305A